PROBLEMS IN THE PROCESSING OF WOOL FIBERS - Turdiyev Rahmatulla Muhammadali o’g’li (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation: This article examines the processing of wool fibers and their problems. The scientific significance of the article lies in the fact that a number of problems in cleaning, washing, drying and processing of wool fibers and spinning from them are mentioned. The article offers a number of solutions to the problems mentioned.